The Relationship of Transformational Leadership and Human Resource Efficiency with the Continuity Approach to Corporate Life (Case study: Eastern Azarbayjan Construction Contractor companies) - Hadi Amini Puya; Ebrahim Salami (مهندسی و مدیریت ساخت)
Construction contractors In spite of Iran’s governmental economic policy and the presence of companies affiliated with government or military and law enforcement agencies in the field of construction projects, have a fairly significant share in this sector. Unlike quasi-governmental contractors that have access to government funds, private sector companies have a fragile structure against economic crises because of their lack of dependence on these funds. This has led to the rise and fall of contracting companies for a limited time and undermines the private contracting community. Although some of the reasons are related to the structural problems of the Iranian economy, the internal factors of the management of these companies are also effective. The present study was conducted in line with the pathology of this subject with the aim of investigating the relationship between transformational leadership and human resource productivity in order to achieve continuity of life of companies in East Azerbaijan. The statistical population of this research is 102 corporate executives, project and site managers of construction projects in East Azerbaijan. The data were collected using two questionnaire including Transformational Leadership (Bass & Avolio), and human resource productivity (Hersey & Goldsmith). The Cronbach's alpha coefficient of all variables is 0.834, which indicates high reliability and validity. The method of this research is descriptive-correlation based on structural equation modeling. Data were analyzed by SPSS software and the results showed that transformational leadership has a direct, positive and strong relationship with human resource productivity to achieve continuity of life of companies.